Electrochemical Deposition of Magnesium on SiC Fibers from the LiCl-KCl-MgCl2 Molten Salt. Issue 9 (20th July 2016) - Chen, Zeng; Li, Shengjun; Wang, Yumin; Li, Wei; Wei, Chaochao; Kong, Wenping; Jia, Xiyang; Pei, Qingqing; Zhang, Weifeng
Abstract : The preparation of Mg/SiC fiber precursor is the key process for the application of SiC fiber in the Mg alloys. Electrochemical deposition method was firstly adopted for the preparation of Mg/SiC fiber precursor in the LiCl-KCl molten salt. However, metal Li will be deposited prior to the deposition of Mg to form Li-C alloys with the carbon layer on the surface of SiC fiber due to the under potential deposition of Li + ion. A Cu intermediate layer was introduced to avoid the formation of Li-C alloys, so that SiC fiber could be stable in a wide electrochemical window in the LiCl-KCl molten salt. A thin Cu layer was coated on SiC fiber using chemical plating method. The effect of NaOH concentration on the Cu coating was investigated and bright Cu coating was obtained. The electrochemical deposition process of Mg 2+ ion was investigated through cyclic voltammetry and the detailed deposition parameters were obtained. Mg/SiC fiber precursor was prepared using pulse current electrodeposition method following the deposition parameters obtained by cyclic voltammetry. The morphology and microstructure of SiC/Mg fiber were explored through SEM. After the optimization of electrodeposition condition, compact and even Mg layer were prepared on SiC fiber.